Clinical correlation between cardiac diabetic autonomic neuropathy (CDAN and nerve ultrasound in polyneuropathy in diabetic patients type 2 (Funded work) - MAHMOUD HASSAN EL-BIDAWY; ABO BAKR OMAR HUSSAIN; MAMDOUH ALI KOTB; MOHAMED A. BEDEWI (International Journal of Pharma and Bio Sciences, 2019)
Diabetic Autonomic Neuropathy (DAN) is a serious and common complication of diabetes. The duration of the QT interval and QT dispersion have emerged as prognostic factors in many clinical settings, such as in post-myocardial infarction and chronic heart failure. . Although imaging analyses for neuropathy patients have not been used for diagnosis, high-resolution diagnostic ultrasound equipment has improved greatly, making detection of minute peripheral nerves by sonographic evaluation possible. Peripheral nerve ultrasonography is increasingly utilized as a complementary method to studies for peripheral nerves assessment. It was found that increased cross-sectional area (CSA) of the median nerve at the wrist and the tibial nerve at the ankle. Diabetic patients type 2 attending the outpatient clinics for cardiology clinic of Prince Sattam Ibn Abdulaziz University Hospital , mostly complaining of postural hypotension in spite of taking their diabetic treatment on a regular basis, CAN Patients accounted for (86.2%) out of chosen 116 diabetic patients. The duration of diabetes for CAN patients was longer (mean 10.4 years ±6.5 SD), the fasting blood sugar was higher in diabetic patients with CAN (Mean=8.8±7 SD), the HbA1c was higher in diabetic patients with CAN (mean 7.6 ±1.4SD), The QTc corrected QT interval dispersion was higher in diabetic patients with CAN (mean 437.4±25.9 SD), the heart rate (HR) variability with deep breathing was highly significantly reduced in diabetic patients with CAN, high-resolution ultrasonography of the median nerves bilaterally revealed that there was increased cross sectional areas of median nerves (mean 15.5 ± 3.2SD) without evidence of clinical polyneuropathy in diabetic patients with CAN and without CAN. This study indicated that CAN is prevalent in type 2 diabetic patients especially with poor glycemic control and long duration of diabetes. The cardiovascular risk factors occurring with CAN are potentially modifiable with good glycemic control early in the disease. Although no clinical evidence of peripheral neuropathy ,there was increased cross-sectional areas (CSA) of median nerves bilaterally as measured by ultrasonography in diabetic patients whether with Can or without Can, which meant that high resolution ultrasonography as a non-invasive easy test to screen cases of diabetes even before clinical symptoms of late diabetic peripheral neuropathy (DPN) occur.